Burnout in Primary Health Care Providers in Mazandaran Province - Khosravi 1, Ahmad; Ranjbar 2, Mansour; Erfan 3, Ali; Sadeghi 4, Zakieh; khojasteh 5, Leyla; Amiri 6*, Mohammad (Shahroud Journal of Medical Sciences, 2018)
Background: Burnout describes negative changes in attitude, mood and behavior in people under work-related stress. This study determines the degree of job burnout inprimary health care providers in Sari, Mazandaran Province, Iran.Methods: This cross-sectional research was conducted on 208 primary health care providers working in Sari in 2015using the Maslach Burnout Inventory. The self-administered questionnaire was completed by the participants and data were analyzed using the Chi-square test. The mean scores of the four dimensions of burnout were calculated using the frequency and intensity scores.Results: A total of 62.9% of the participants were female and a majority was married (91%). Approximately 21% of the participants were completely satisfied with their essential workplace facilities. The mean scores of the intensity and frequency of emotional exhaustion were 17.19±14.65 and 15.84±12.27. The mean scores of the intensity and frequency of the lack of personal accomplishment were 36.8±12.17 and 30.34±9.72. As for depersonalization, the mean scores of intensity and frequency were 4.22±5.36 and3.95±4.53. The mean scores of the intensity and frequency of conflict were 6.67±5.12 and 6.18±4.26. The mean scores of the intensity and frequency of overall burnou twere also 64.89±22.95 and 56.31±19.87. There were significant relationships between the intensity and frequency of overall burnout and dissatisfaction with work experience, income, interest in the job and workplace facilities (P<0.05).Conclusions: Given the relationship between job burnout and variables including income and essential workplace facilities, it is imperative to improve health care providers’payment and salary and provide them with any essential facilities at their workplace and enable career advancement so as to help reduce burnout in different dimensions.